Development of batik surface design layout using pattern grading arrangement for contemporary women’s baju kurung - Che Ya, Mohamad Shukri (2024)
The Malaysian batik and fashion industry plays a crucial role in the country’s economy. To ensure its continued growth, it’s essential for batik fabric manufacturing to adopt modern methods and technology. However, a lack of research on batik fabric, particularly regarding pattern grading arrangement for contemporary women’s baju kurung and motif design placement layout, poses challenges for tailors, leading to fabric wastage. This research examines a new batik surface design layout by investigating suitable pattern grading arrangement for contemporary women’s baju kurung. In order to collect data for this research study, a comprehensive approach was adopted, consisting of interviews, observations, experiments, and validation through the utilisation of focus group interviews and Likert scale questionnaires. 10 expertise were interviewed for the research where 3 batik experts, 2 batik tailors and 5 batik sellers. Besides, 4 batik markets and craft festivals were chosen for observations and 23 samples were produced in experiments. Meanwhile, 6 batik experts and textile or batik lecturers were involved in validation (focus group interview) and 13 expertise were involved in validation (questionnaire) where 9 batik experts and 4 fashion experts. The findings indicate that experts in batik and fashion strongly endorse the innovative batik surface design fabric arrangement layout, which showcases innovation and sustainability by reducing fabric consumption compared to existing batik fabric and its pattern grading arrangement meets aesthetic and functional standards. Furthermore, the research recommended a new batik surface design layout based on pattern grading arrangement for use by manufacturers or designers during the development and production of contemporary women’s baju kurungs.